Oxygen-generating electrode catalyst, anode electrode, and oxygen-generating device
A non-noble metal catalyst composed of manganese, iron, nickel, zinc, and silver oxides addresses the cost and resource limitations of platinum group elements, providing efficient and durable oxygen generation for green hydrogen production.
Patent Information
- Application Number
- JP2023108300
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Current electrode catalysts for oxygen generation in green hydrogen production, such as those using platinum group elements, are expensive and have limited resources, necessitating the development of a low-cost, non-noble metal catalyst with high efficiency and long life.
An electrode catalyst composed of oxides of manganese, iron, nickel, zinc, and silver, optionally with chlorine, is used for oxygen generation, which is produced through a pyrolysis process on a conductive substrate, offering high oxygen generation efficiency, stability, and durability.
The catalyst achieves low cost, high oxygen generation efficiency, and long life, maintaining excellent overvoltage, stability, and current density characteristics in slightly alkaline pH regions, outperforming noble metal alternatives.
Smart Images

Figure 2025007110000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode catalyst for oxygen generation, an anode electrode, and an apparatus for generating oxygen. [Background technology]
[0002] In recent years, green hydrogen has been attracting attention as a clean energy source to replace fossil fuels in light of global environmental issues such as global warming. Green hydrogen is an environmentally friendly energy source that does not emit carbon dioxide during its production or use.
[0003] Since green hydrogen is produced by the electrolysis of water, an oxygen-evolving electrode catalyst is essential for producing green hydrogen. Currently, precious metals such as platinum group elements platinum (Pt), ruthenium (Ru) or iridium (Ir) are mainly used as electrode catalysts for oxygen generation, as disclosed, for example, in Patent Document 1. However, these precious metal elements are expensive and resources are limited, which is an obstacle to supplying a huge amount of green hydrogen. For this reason, there is a demand for a low-cost electrode catalyst for oxygen generation that is made of a non-noble metal, has high oxygen generation efficiency, and has a long life. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-37942 A [Non-patent literature]
[0005] [Non-Patent Document 1] Xie, M. et al. An amorphous Co-carbonate-hydroxide nanowire array for efficient and durable oxygen evolution reaction in carbonate electrolytes. Nanoscale 9, 16612-16615 (2017) [Non-Patent Document 2] Xie, F. et al. Ni3N@Ni-Ci nanoarray as a highly active and durable non-noble-metal electrocatalyst for water oxidation at near-neutral pH. Journal of Catalysis 356, 165-172 (2017). [Non-Patent Document 3] Ma, M. et al. Highly efficient and durable water oxidation in a near-neutral carbonate electrolyte electrocatalyzed by a core-shell structured NiO@Ni-Ci nanosheet array. Sustainable Energy & Fuels 1, 1287-1291 (2017). [Non-Patent Document 4] Wang, N. et al. Hydration-Effect-Promoting Ni-Fe Oxyhydroxide Catalysts for Neutral Water Oxidation. Advanced Materials 32, 1906806 (2020). [Non-Patent Document 5] Chen, L., Ren, X., Teng, W. & Shi, P. Amorphous Nickel-Cobalt-Borate Nanosheet Arrays for Efficient and Durable Water Oxidation Electrocatalysis under Near-Neutral Conditions. Chemistry - A European Journal 23, 9741-9745 (2017). [Non-Patent Document 6] Yang, L. et al. A cobalt-borate nanosheet array: an efficient and durable non-noble-metal electrocatalyst for water oxidation at near neutral pH. Journal of Materials Chemistry A 5, 7305-7308 (2017). [Non-Patent Document 7] Ji, X. et al. Core-shell CoFe2O4@Co-Fe-Bi nanoarray: a surface-amorphization water oxidation catalyst operating at near-neutral pH. Nanoscale 9, 7714-7718 (2017). [Non-Patent Document 8] Dong, Y., Komarneni, S., Wang, N., Hu, W. & Huang, W. An in situ anion exchange induced high-performance oxygen evolution reaction catalyst for the pH-near-neutral potassium borate electrolyte. Journal of Materials Chemistry A 7, 6995-7005 (2019). [Non-Patent Document 9] Liu, X. et al. Nanostructured copper oxide electrodeposited from copper(II) complexes as an active catalyst for electrocatalytic oxygen evolution reaction. Electrochemistry Communications 46, 1-4 (2014).
Non-Patent Document 10
Non-Patent Document 11
Non-Patent Document 12
[0006] An object of the present invention is to provide a non-noble metal electrode catalyst which has high oxygen generation efficiency, a long life, and is also low in cost. [Means for solving the problem]
[0007] The configuration of the present invention for solving the problems is shown below.
[0008] (Configuration 1) A non-precious metal electrode catalyst for oxygen evolution consisting of a mixture of oxides containing manganese, iron, nickel, zinc, and silver. (Configuration 2) An electrode catalyst for oxygen evolution consisting of a mixture of oxides of manganese, iron, nickel, zinc, and silver. (Configuration 3) An electrode catalyst for oxygen evolution, comprising an oxide mixture of an alloy of manganese, iron, nickel and zinc, and silver nanoparticles. (Configuration 4) The composition is MnFeNiZn 0.5 AgO x 4. The electrode catalyst for oxygen evolution according to claim 2 or 3, (Configuration 5) 5. The electrode catalyst for oxygen evolution according to any one of claims 1 to 4, further comprising chlorine. (Configuration 6) An anode electrode using the electrode catalyst for oxygen evolution according to any one of configurations 1 to 5. (Configuration 7) An oxygen generating device comprising the anode electrode according to configuration 6. Effect of the Invention
[0009] The present invention provides a non-precious metal electrocatalyst that has high oxygen generation efficiency, a long life, and is also low cost. [Brief description of the drawings]
[0010] [Figure 1] 1 is a SEM (Scanning Electron Microscope) photograph of a sample prepared in an example. [Diagram 2] 1 shows XRD (X-Ray Diffraction) data of samples prepared in the examples. [Diagram 3]These are the results of structural evaluation of the MnFeNiZn0.5AgOx sample prepared in the example. (a) is a low-magnification HR-TEM (High-Resolution Transmission Electron Microscope) image, (b) is a high-magnification HR-TEM image, (c) is an electron beam diffraction image of the area indicated by the circle, (d) is an ADF-STEM (Annular Dark-Field Scanning Transmission Electron Microscope) image, and (e) to (k) are observations of the spatial distribution of the component elements by EDS (Energy Dispersive Spectroscopy), where (e) is Mn, (f) is Fe, (g) is Ni, (h) is Zn, (i) is Ag, (j) is O, and (k) is Ti. [Figure 4] The results of XPS (X-ray photoelectron spectroscopy) measurements of the MnFeNiZn0.5AgOx sample prepared in the examples are shown here, along with the calculation results obtained by fitting the spectra corresponding to the actual measurements, (a) Mn 2p, (b) Fe 2p, (c) Ni 2p3 / 2, (d) Zn 2p3 / 2, (e) Ag 3d, and (f) O 1s. [Diagram 5] FIG. 1 is a characteristic diagram showing the overvoltage at a current density of 10 mA / cm2 for various materials including MnFeNiZnAg. [Figure 6] This is a characteristic diagram evaluating the oxygen evolution reaction of the MnFeNiZn0.5AgOx electrode catalyst in terms of the time dependence of potential, with pH as a parameter. [Figure 7] This is a characteristic diagram of the oxygen evolution reaction of the MnFeNiZn0.5AgOx electrode catalyst material evaluated by the potential-current characteristics (LSV curve) in an environment of 80°C using a 1M carbonate (Na-Ci) electrolyte. [Figure 8] This is a characteristic diagram comparing and evaluating the potential change over time (CP: Chronopotentiometry) of MnFeNiZn0.5AgOx and RuO2. [Figure 9] FIG. 1 is a Ragony plot showing, in map form, the relationship between current density and specific charge for various materials. [Figure 10] FIG. 2 is a configuration explanatory diagram illustrating the main configuration of the oxygen generating device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] (Embodiment 1) In the first embodiment, the electrode catalyst of the present invention will be described.
[0012] The oxygen evolution electrode catalyst (electrode catalyst) of the present invention is an oxide of a mixture containing manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn), and silver (Ag), and is made of a material that does not contain precious metals. Alternatively, the electrode catalyst of the present invention is an oxide of a mixture of manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn), and silver (Ag). Here, the electrode catalyst of the present invention may be a mixture of an alloy of manganese, iron, nickel, and zinc, and silver nanoparticles. In particular, MnFeNiZn, in which the atomic composition ratio of Mn, Fe, Ni, Zn and Ag is Mn:Fe:Ni:Zn:Ag=1:1:1:0.5:1, 0.5 MnFeNiZn, an oxide of Ag 0.5 AgO x is an oxygen evolution electrode catalyst having excellent characteristics such as overvoltage, durability, and large current characteristics in a weakly alkaline pH region. Here, the amount of oxygen may be the amount due to natural oxidation in the atmosphere.
[0013] The electrode catalyst of the present invention uses metal elements that are abundant and relatively low in cost, and does not contain rare and expensive precious metals such as platinum (Pt) and ruthenium (Ru), thereby enabling costs to be reduced. Furthermore, by using the above-mentioned material configuration, a catalyst for oxygen generation electrodes is obtained that has excellent overvoltage, stability, durability, current density characteristics, specific charge, and large current characteristics in the weakly alkaline pH range, as shown in the examples.
[0014] The oxygen evolution electrode catalyst (electrode catalyst) of the present invention can be obtained through a pyrolysis process in which a solution containing manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn) and silver (Ag) is prepared and mixed, the mixture is applied to a conductive substrate such as titanium (Ti) by coating, and then the substrate is dried and fired. Here, the solution containing manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn) and silver (Ag) is, for example, MnCl 2 , FeCl 2 , ZnCl 2 , AgCl, etc., and AgNO 3 In this case, some of the chlorine (Cl) used in the solution remains in the electrode catalyst, but it has been confirmed that this does not adversely affect the electrode catalyst's characteristics such as overvoltage and stability. By using a chloride solution, an oxygen generating electrode catalyst can be efficiently and easily produced. Regarding Ag, AgNO 3 can be used with preference. The sintering temperature is preferably 150° C. or higher and 400° C. or lower. Other methods for producing the electrode catalyst of the present invention include electrodeposition, chemical vapor deposition, hydrothermal synthesis, and solvothermal methods.
[0015] (Embodiment 2) In the second embodiment, an oxygen generating device 101 using the oxygen generating electrode catalyst explained in the first embodiment and an anode electrode (oxygen electrode) 12 used therein will be described with reference to FIG.
[0016] 10, the oxygen generating device 101 is equipped with an anode electrode (oxygen electrode) 12 and a cathode electrode (hydrogen electrode) 13, and its main components are an electrolytic cell 11 filled with water 14 containing an electrolyte, an oxygen gas separation tower 16, a dehumidifier 17, a water tank 18, a hydrogen gas separation tower 19, and a dehumidifier 20. A power source 15 is connected to the anode electrode 12 so that a positive voltage is applied to the cathode electrode 13, and a negative voltage is applied to the cathode electrode 13.
[0017] Water 14 is electrolyzed by applying a voltage to the anode electrode 12 and the cathode electrode 13 , and oxygen gas and hydrogen gas are generated within the electrolytic cell 11 . The generated oxygen gas is transported together with water vapor to the oxygen gas separation tower 16, where the moisture and oxygen gas are separated. The separated water is poured into a water tank 18, and the oxygen gas is dehumidified by a dehumidifier 17 to remove oxygen (O 2 ) is recovered. Here, the separation of oxygen gas or oxygen gas from water can be performed using a density difference separation method that separates water, which is a high-density liquid, from gas, which is low-density, by the action of gravity or collision force, and / or a gas-liquid separation method that utilizes the surface tension of the liquid.
[0018] The generated hydrogen gas is transported together with water vapor to the hydrogen gas separation tower 19, where the moisture and hydrogen gas are separated. The separated water is poured into the water tank 18, and the hydrogen gas is dehumidified by the dehumidifier 20 to obtain hydrogen (H 2 The water supplied via the pipe 21 and the water poured from the oxygen gas separation tower 16 and the hydrogen gas separation tower 19 are returned to the electrolytic cell via the water tank 18.
[0019] Here, the anode electrode 12 is an electrode using an electrode catalyst made of a non-precious metal material made of an oxide of a mixture containing manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn), and silver (Ag) as described in embodiment 1, or an oxide of a mixture made of manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn), and silver (Ag). That is, as the anode electrode 12, an electrode in which the material described in embodiment 1 is deposited on a collector electrode substrate such as titanium, or an electrode made of the material described in embodiment 1 is used.
[0020] The oxygen generating device 101 equipped with the anode electrode 12 using the oxygen generating electrode catalyst described in embodiment 1 is an oxygen generating device 101 that has excellent characteristics such as overvoltage, stability, durability, current density characteristics, specific charge, and large current characteristics in the weakly alkaline pH range, has high oxygen generating efficiency, a long life, and is also low in cost. EXAMPLES
[0021] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0022] 1. Electrocatalyst Preparation An electrode catalyst made of a mixture of oxides of manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn), and silver (Ag) was prepared by the following process. In addition, as a reference example, titanium (Ti) was used instead of Mn. 0.5 FeNiZnAg oxide, Sc using scandium (Sc) instead of Zn 0.5 The oxide of MnFeNiAg was also prepared.
[0023] First, 0.05M MnCl 2 , FeCl 2 , NiCl 2 , ZnCl 2 and AgNO 3 Each solution was prepared. For reference, 0.05M TiCl 2 , ScCl 2 Solutions were also prepared. Next, the solutions were mixed according to the ratio. 0.5 AgO x The preparation of MnCl 2 :FeCl 2 :NiCl 2 :ZnCl 2 :AgNO 3 Mixed in a ratio of 1:1:1:0.5:1. The mixture was then drop-cast onto a Ti substrate measuring approximately 0.5cm x 2.0cm x 0.01cm, dried at room temperature (approximately 25°C), and pre-sintered in an oven at 350°C for 10 minutes. This step of drop-casting the mixture and pre-sintering was repeated nine times, and then sintered at 450°C for one hour to produce an electrode coated with an electrode catalyst containing five types of metals on a Ti substrate. Here, the pre-sintering and sintering were performed in air. Thus, oxidation was achieved by natural oxidation, pre-sintering, and sintering.
[0024] For comparison, RuO 2 A metal oxide catalyst was prepared. RuO 2 Metal oxide catalysts were prepared by mixing the above five metal solutions in a 0.05M solution of RuCl 3 Replace with RuO and follow the above procedure for the rest. 2 A catalyst coated electrode was prepared. The mass loading of the electrode coated with the electrocatalyst on the Ti substrate was approximately 0.13 mg for all samples.
[0025] 2. Characterization 2.1 Material characterization The SEM (Scanning Electron Microscope) photographs of the prepared electrode samples are shown below. 0.5 AgO x An example is shown in Figure 1. Nanoparticles can be seen, and the surface has irregularities. Here, an SU8000 (manufactured by Hitachi) was used as the SEM. XRD (X-ray Diffraction) measurements of each sample revealed that the crystal structure of the prepared samples consisted of cubic silver chloride with space group Fm-3m and hexagonal nickel oxide with space group R-3m, as shown in Figure 2. A MiniFlex X-ray diffractometer (manufactured by Rigaku) was used for the measurements. The results of observing the sample using a cross-sectional high-resolution transmission electron microscope (HR-TEM) are shown in Fig. 3(a). 0.5 AgO x The average thickness of the nanoparticles was 978.0±139.8 nm. As the black spots were observed, it was found that the nanoparticles were composed of nanoparticles. The HR-TEM used was JEM-2100F1 (manufactured by JEOL).
[0026] The results of detailed observation by Selected Area Electron Diffraction (SAED) are shown in Figures 3(b) and (c), which indicate that the materials other than the AgCl crystals are mainly amorphous or low-crystalline materials. The main SAED pattern, as shown in Figure 3(c), corresponds to the three-dimensional structure of AgCl, and this result is in good agreement with the XRD measurement result shown in Figure 2. MnFeNiZn 0.5 AgO x The results of observation with an annular dark field-scanning transmission electron microscope (ADF-STEM) are shown in Figure 3(d), and the results of element mapping using energy dispersive spectroscopy (EDS) are shown in Figures 3(e)-(k). Here, Figures 3(e), (f), (g), (h), (i), (j), and (k) show the distribution of Mn, Fe, Ni, Zn, Ag, O, and Ti elements, respectively. These results indicate that the elements Mn, Fe, Ni, Zn and O are uniformly distributed throughout the electrocatalyst. On the other hand, most of the Ag element is in the form of nanoparticles, with only a small amount forming metal oxides with other metal species and dispersed therein. The ADF-STEM used was JEM-ARM200F-B (manufactured by JEOL).
[0027] Next, high-resolution X-ray photoelectron spectroscopy (XPS) was used to characterize the MnFeNiZn 0.5 AgO x The chemical composition and oxidation state of each element were investigated. The results are shown in Figure 4. Here, a Quantera SXM (Ulvac-PHI) was used for XPS. As a result, MnFeNiZn 0.5 AgO xThe XPS measurement results confirmed that the sample contains seven elements: Mn, Fe, Ni, Zn, Ag, Cl, and O. Figure 4 shows the spectra of the six elements: Mn, Fe, Ni, Zn, Ag, and O. As shown in FIG. 4(a), Mn 3+ 641.9 eV (Mn 2p 3 / 2 ) and 653.6 eV (Mn 2p 1 / 2 ), and Mn 4+ 646.7 eV (Mn 2p 3 / 2 ) and 658.4 eV (Mn 2p 1 / 2 ) and Fe has two oxidation states, Fe 2 , as shown in Fig. 4(b). 2+ 711.0 eV (Fe 2p 3 / 2 ) and 724.1 eV (Fe 2p 1 / 2 ), and Fe 3+ 713.0 eV (Fe 2p 3 / 2 ) and 726.1 eV (Fe 2p 1 / 2 ) It consists of two oxidation states. Ni 2p 3 / 2 As shown in Fig. 4(c), 2+ 856.2 eV and Ni 3+ It consists of two states at 858.9 eV, Zn 2p 3 / 2 As shown in Fig. 4(d), Zn 2+ 1022.0 eV and Zn 0 It consists of two states at 1023.6 eV. As shown in Figure 4(e), Ag 2+ 367.3 eV (Ag 3d 5 / 2 ) and 373.3 eV (Ag 3d 3 / 2 ), and Ag + 368.1 eV (Ag 3d 5 / 2 ) and 374.1 eV (Ag 3d 3 / 2 ) It consists of two oxidation states.
[0028] From the above results, MnFeNiZn 0.5 AgO x The sample contains five metal elements, Mn, Fe, Ni, Zn, and Ag, each of which has multiple valence states.4+ Or Ag 2+ It was shown that the valence states of MnFeNiZn and other species are mainly distributed in the valence state. This forms a highly active material, 0.5 AgO x It is presumed that this is the basis for the high oxygen evolution reaction.
[0029] In addition, as shown in Fig. 4(f), the O 1s spectrum was calculated by subtracting the lattice oxygen (O L ), and oxygen vacancy (O V ) and 533.7 eV surface adsorbed oxygen / interlayer water (O W ) and deconvolution analysis is performed, 0.5 AgO x The oxygen (O) in the sample is oxygen vacancy (O V The area ratio of oxygen vacancies in the MnFeNiZn alloy was as high as 48 atomic %, indicating that the sample had a large number of oxygen vacancies. 0.5 AgO x It is presumed that this is one of the reasons why the oxygen evolution reaction is so high.
[0030] 2.2 Electrochemical characterization MnFeNiZnAgO x , MnFeNiZn 0.5 AgO x and MnFeNiZnAg 0.5 O x MnFeNiZnAgO x Based materials and Ti as a reference material 0.5 FeNiZnAgO x and Sc 0.5 MnFeNiAgO x Regarding the material, its 10mA / cm 2 The overpotential at 1000 kV was evaluated. The measurement was carried out using a three-electrode beaker cell consisting of a working electrode with the above-mentioned material placed thereon, a reference electrode, and a counter electrode, and 0.1 M KOH as the electrolyte. The reference electrode was a silver-silver chloride electrode, and the counter electrode was platinum. As is clear from the results shown in Figure 5, MnFeNiZnAgO xThe MnFeNiZn system material has a lower overpotential than the reference material and has excellent properties as an electrode catalyst for oxygen evolution. 0.5 AgO x had the lowest overvoltage of 0.42 V and the most excellent overvoltage characteristics.
[0031] Next, MnFeNiZn 0.5 AgO x The electrochemical stability of the samples was evaluated by chronopotentiometry. 2 The time dependence of the voltage E at which the hydrogen peroxide is obtained was evaluated by controlling the pH of the electrolyte with a buffer solution. Here, the voltage E is the voltage applied to a reversible hydrogen electrode (RHE). As is clear from the results shown in Figure 6, in an electrolyte environment controlled at pH ≦ 8 with phosphate buffer, the voltage E increased rapidly within 1 hour. 0.5 AgO x It has been confirmed that the electrode made of the sample deteriorates rapidly during the oxygen evolution reaction, causing Mn, Fe and Ni to dissolve and flow into the electrolyte. On the other hand, in an electrolyte environment controlled to an alkaline pH of 9.2 or higher using carbonate or KOH buffers, the current is 50 mA / cm 2 The high durability and stability of the sample have been ensured, allowing it to maintain this temperature for more than three hours. It has been confirmed that the distribution and composition of all the elements in this sample remain almost unchanged before and after the experiment.
[0032] The electrochemical stability can be significantly enhanced by controlling the electrolyte environment at 80° C. and pH 9.2 with 1.0 M Na-Ci buffer. Figure 7 shows the MnFeNiZn 0.5 AgO x The results of LSV (Linear Sweep Voltammetry) measurements performed on the sample under these conditions are shown below. The voltage E was 2.6 V relative to RHE, and the current was 1000 mA / cm. 2 was obtained.
[0033] Figure 8 shows the results of the MnFeNiZn 0.5 AgO x The sample was evaluated by chronopotentiometry, where the current was 400 mA / cm 2 The temperature was set to 0°C, and the electrolyte was added at the timing indicated by the arrow. 2 The results of are also shown as comparative examples. As is clear from FIG. 0.5 AgO x The sample was 400mA / cm 2 The voltage E was stable for more than 600 hours at 1000 V. On the other hand, the voltage E of RuO 2 In the sample, the voltage E changed rapidly after 7 hours, and the MnFeNiZn 0.5 AgO x The superiority of the sample was confirmed.
[0034] Figure 9 is a visualization of the current density and specific charge of various oxygen evolution electrode catalysts as a map. Since oxygen evolution electrode catalysts are desired to have high current density and specific charge, the materials in the upper right corner are desirable. From Figure 9, MnFeNiZn 0.5 AgO x It can be seen that this material has excellent current density and specific charge characteristics as an electrode catalyst for oxygen evolution. The electrolyte environment and citations for each characteristic evaluation are summarized in Table 1.
[0035] [Table 1]
[0036] From the above examples, it is clear that the oxide of a mixture of manganese, iron, nickel, zinc, and silver, particularly MnFeNiZn 0.5 AgO x It was confirmed that this material has excellent properties as an electrode catalyst for oxygen evolution. [Industrial Applicability]
[0037] Metal catalysts for oxygen generation are used in equipment that produces green hydrogen, which is seen as the next-generation energy source, and are also applied to fuel cells, FCVs, etc. The present invention provides a metal catalyst with high oxygen generation efficiency without using platinum group precious metal elements, which are rare, expensive, and limited in resource. It is expected that this will support next-generation industry and society, regardless of whether it is for consumer or industrial use, and greatly contribute to their development. [Explanation of symbols]
[0038] 11: Electric field cell 12: Anode electrode (oxygen electrode) 13: Cathode electrode (hydrogen electrode, RHE) 14: Water (H 2 O) 15: Power supply 16: Oxygen gas separation tower 17:Dehumidifier 18: Water tank 19: Hydrogen gas separation tower 20:Dehumidifier 21: Piping
Claims
1. A non-precious metal electrode catalyst for oxygen evolution consisting of a mixture of oxides containing manganese, iron, nickel, zinc, and silver.
2. An electrode catalyst for oxygen evolution consisting of a mixture of oxides of manganese, iron, nickel, zinc, and silver.
3. An electrode catalyst for oxygen evolution, comprising an oxide mixture of an alloy of manganese, iron, nickel and zinc, and silver nanoparticles.
4. The composition is MnFeNiZn 0.5 AgO x 4. The electrode catalyst for oxygen evolution according to claim 2 or 3,
5. The electrode catalyst for oxygen evolution according to claim 1 , further comprising chlorine.
6. An anode electrode using the electrode catalyst for oxygen evolution according to any one of claims 1 to 5.
7. An oxygen generating device comprising the anode electrode according to claim 6.
Citation Information
Patent Citations
Method for producing fuel cell electrode catalyst, fuel cell electrode catalyst and use of the same
JP2013037942A